2018
DOI: 10.1111/ajag.12576
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot testing of the revised Patients’ Attitudes Towards Deprescribing questionnaire for people with cognitive impairment

Abstract: The rPATDcog was feasible to administer in this study. Further work is required to provide generalisable results and determine utility in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Questionnaires to capture how patients feel about deprescribing: Patients’ Attitudes Towards Deprescribing (PATD) questionnaire (revised in 2016, versions for older adults, caregivers and people with cognitive impairment) Patient Perceptions of Deprescribing (PPoD) survey …”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires to capture how patients feel about deprescribing: Patients’ Attitudes Towards Deprescribing (PATD) questionnaire (revised in 2016, versions for older adults, caregivers and people with cognitive impairment) Patient Perceptions of Deprescribing (PPoD) survey …”
Section: Introductionmentioning
confidence: 99%
“…Also, caregivers of persons with or without dementia are important contributors to understanding of a person's goals and preferences for medications. A study found that there was a good level of agreement between people with dementia and their carers about attitudes towards deprescribing . A CCDSS that incorporates tools that are appropriate for residents, including those living with dementia, and their caregivers, has the potential to facilitate discussions about a person's goals and preferences for medications between consumers and health‐care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that there was a good level of agreement between people with dementia and their carers about attitudes towards deprescribing. 12 A CCDSS that incorporates tools that are appropriate for residents, including those living with dementia, and their caregivers, has the potential to facilitate discussions about a person's goals and preferences for medications between consumers and health-care professionals. This qualitative study shows limited understanding of what goals of care are and the lack of motivation to initiate conversations with residents and their caregivers.…”
Section: Sub-theme Description Example Of Quotementioning
confidence: 99%
See 2 more Smart Citations